SEMANTIC- THEMATIC TYPES OF HYPERBOLE - Yusupova, S (Журнал иностранных языков и лингвистики, 2021)
The article deals with semantic-thematic types of hyperbole as a SD in the English language. According to scientists points of view the main semantic characteristic of hyperbole is the property of emotionality. Hyperboles expressing negative emotions through such themes as fear, anger and resentment, death, destruction, also the expression of positive emotion joy, surprise caused by quantity, distance, time, characteristics of man, his desire and action have been analyzed in the examples taken from literary texts.